INTERLAYER SHIFTS OF TWO-LAYER COMPOSITE REINFORCED PLATES AND SHELLS TAKING INTO ACCOUNT TEMPERATURE LOADS - C.T.S Dusmatov A.D; Abdullaev R.R (Western European Studies, 2025)
Combined plates and shells consisting of two layers interconnected by a pliable thin adhesive seam under the influence of external temperature loads are considered. It is found that the shear modulus and the thickness of the seam have a great influence on the strength and deformability of combined double-layer shells, especially during thermal heating
Keywords: Combined two-layer plate and shell; interlayer shifts; temperature load